2012
DOI: 10.1021/jp212136r
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of n-Butoxy and 2-Pentoxy Isomerization and Detection of Primary Products by Infrared Cavity Ringdown Spectroscopy

Abstract: The primary products of n-butoxy and 2-pentoxy isomerization in the presence and absence of O(2) have been detected using pulsed laser photolysis-cavity ringdown spectroscopy (PLP-CRDS). Alkoxy radicals n-butoxy and 2-pentoxy were generated by photolysis of alkyl nitrite precursors (n-butyl nitrite or 2-pentyl nitrite, respectively), and the isomerization products with and without O(2) were detected by infrared cavity ringdown spectroscopy 20 μs after the photolysis. We report the mid-IR OH stretch (ν(1)) abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 90 publications
2
17
0
Order By: Relevance
“…The rate coefficient for isomerization of n -C 4 H 9 O is sufficiently higher, k n7 (760) = 1.8 × 10 5 s –1 , as obtained by averaging the results from the recent PLP-CRDS study of Sprague et al and the studies referenced herein. It is necessary to note that the k n7 values were determined from the relative k n7 / k n5 measurements, assuming k n5 = 9.5 × 10 –15 cm 3 molecule –1 s –1 for the reference reaction with oxygen recommended by Atkinson, which seems to be more reliable than the more recent recommendation of 1.4 × 10 –14 cm 3 molecule –1 s –1 , as the latter is based on the results of Morabito and Heicklen extracted from the relative k n5 / k n6 measurements using an early generic k n6 value of 4.4 × 10 –11 cm 3 molecule –1 s –1 , while new results give k n6 = 3.2 × 10 –11 cm 3 molecule –1 s –1 .…”
Section: Experimental Methodssupporting
confidence: 53%
“…The rate coefficient for isomerization of n -C 4 H 9 O is sufficiently higher, k n7 (760) = 1.8 × 10 5 s –1 , as obtained by averaging the results from the recent PLP-CRDS study of Sprague et al and the studies referenced herein. It is necessary to note that the k n7 values were determined from the relative k n7 / k n5 measurements, assuming k n5 = 9.5 × 10 –15 cm 3 molecule –1 s –1 for the reference reaction with oxygen recommended by Atkinson, which seems to be more reliable than the more recent recommendation of 1.4 × 10 –14 cm 3 molecule –1 s –1 , as the latter is based on the results of Morabito and Heicklen extracted from the relative k n5 / k n6 measurements using an early generic k n6 value of 4.4 × 10 –11 cm 3 molecule –1 s –1 , while new results give k n6 = 3.2 × 10 –11 cm 3 molecule –1 s –1 .…”
Section: Experimental Methodssupporting
confidence: 53%
“…In a new variation on the cavity ring-down approach, Okumura and co-workers 36 have detected hydroxyl-peroxy radicals in the OH fundamental stretching region. The radicals were formed following the isomerization of C4 and C5 alkoxy radicals, followed by addition of O 2 to the resultant hydroxyalkyl radicals.…”
Section: Advances In the Detection Of Peroxy Radicalsmentioning
confidence: 99%
“…We detected intermediates and primary products by IR-CRDS, with 10 μs temporal resolution. Our PLP-IR-CRDS apparatus has been described in detail elsewhere; , here, we present a brief overview of the apparatus. A schematic of the laser system can be found in the Supporting Information.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…We have shown that pulsed Infrared cavity ringdown spectroscopy (IR-CRDS) provides a sensitive means for the selective detection of transient intermediates in the mid-IR, especially in the OH stretch region. We have detected reactive intermediates and primary products of free radical reactions in time-resolved flow cell experiments, including the initial HOONO and HONO 2 products formed from the reaction of • OH + NO 2 • , and the 4,1-hydroxy-butyl and 4,1-hydroxy-butyl-peroxy radicals formed from the isomerization of the n- butoxy radical. …”
Section: Introductionmentioning
confidence: 99%